1998
DOI: 10.1002/(sici)1097-4628(19980912)69:11<2115::aid-app3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial take-up speed on properties and structure of as-spun and drawn/heat-set poly(ethylene terephthalate) filaments

Abstract: ABSTRACT:The effect of initial take-up speed on the properties and structure of both as-spun and drawn/heat-set poly(ethylene terephthalate) filaments was characterized through measurements of birefringence, percent crystallinity, tensile properties, high temperature shrinkage, loss tangent temperature dependence, DSC melting behavior, and wide-angle (WAXS) and small-angle X-ray scattering (SAXS). While a steady trend toward improved as-spun filament orientation and tensile properties occurred with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Studies of nylon, polyethylene, and poly(ethylene terephthalate) fibers have shown that orientation and other characteristics of the noncrystalline or amorphous phase also influence the polymer performance. [1][2][3][4][5][6][7][8] In addition, interactions between the crystalline and amorphous regions are also expected to significantly affect the polymer properties. [6][7][8][9][10][11][12][13] Connectivity between the crystalline stems and the amorphous chain segments is often invoked to explain the correlation between lamellar spacings and unit cell dimensions 14 and the decrease in the unit cell volume of the crystals within the lamellae as the amorphous regions swell when exposed to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of nylon, polyethylene, and poly(ethylene terephthalate) fibers have shown that orientation and other characteristics of the noncrystalline or amorphous phase also influence the polymer performance. [1][2][3][4][5][6][7][8] In addition, interactions between the crystalline and amorphous regions are also expected to significantly affect the polymer properties. [6][7][8][9][10][11][12][13] Connectivity between the crystalline stems and the amorphous chain segments is often invoked to explain the correlation between lamellar spacings and unit cell dimensions 14 and the decrease in the unit cell volume of the crystals within the lamellae as the amorphous regions swell when exposed to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the tenacity and max force increased with the cooling temperature till 150 C, and then decreased rapidly at 200 C. Polymer filaments, when pulled above their glass transition temperature, straightens, and the polymer structure turns more crystalline, resulting in a decrease in their linear density. 20,23 R1 and R2, set at 220 C, is above the glass transition temperature of the polymer and hence deforms the polymer structure of the filament. The eventual structure of the polymer is dictated by the cooling temperature in R3 and R4.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern consists of only rings and is devoid of any dots, indicating that the filament is amorphous. 20 The mechanical properties of PEI filaments were analyzed by estimating their tensile strength (Figure 2e). The as-spun PEI filament was found to possess a linear density of 74.08 den and a yield strength of 1.41 cN/den at 7.9% strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation